Engineered whole cut meat-like tissue by the assembly of cell fibers using tendon-gel integrated bioprinting - Dong-Hee Kang (Nature Portfolio, 2021)
Mammalian cell-based cultured meat has mostly been unstructured, leaving a demand for artificial steak-like meat. Here the authors present an assembled steak-like tissue of bovine skeletal muscle, adipose tissue, and blood capillary tissue fabricated by tendon-gel integrated printing technology.